Competitive Advantage Analysis Of MSMES In The Culinary Sector: Reviewing The Influence Of Market Orientation And Green Supply Chain Management - Sudirman, Acai; Sinaga, Onita Sari; Julyanthry, Julyanthry; Grace, Ernest (Journal of Business and Management Inaba, 2024)
Market orientation, which includes understanding consumer needs, responding to competitors, and coordinating between business functions, is considered a factor that can improve the competitiveness of MSMEs by better adjusting their products and services to consumer preferences. On the other hand, implementing green supply chain management, which focuses on environmentally friendly practices throughout the supply chain, can improve the company's image and operational efficiency, thereby providing a more sustainable competitive advantage. This study aims to analyze the effect of market orientation and green supply chain management on competitive advantage in culinary sector MSMEs. Through survey methods and regression analysis, this study attempts to find the relationship between these variables in the context of MSMEs. The study results concluded that market orientation and green supply chain management positively and significantly affect the competitive advantage of culinary sector MSMEs. These findings are expected to provide insight for MSMEs in the culinary sector about the importance of adopting market orientation and green supply chain management strategies to strengthen their competitive position amidst increasingly tight competition and increasing consumer environmental awareness.